METHODS OF ORGANIZING INTERNATIONAL MARKETING ACTIVITIES OF FIRMS - Elena Shatskaya (Вестник Северо-Кавказского федерального университета)
The paper examines the importance and role of marketing activities in modern economic conditions, shows the feature of marketing activities in the international market. The importance in modern practice of the marketing approach; the role of management; clarified the principles underlying the marketing approach. The use of a systematic approach to the management of international marketing activities of the company allows us to explore the object as a set of interrelated subsystems with certain internal and external relations: a model of management of international marketing activities of the company.